2023
DOI: 10.1177/08980101231217358
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Quality of Life with Education-Based Treatment for Hypertension Patients During COVID-19 Adaptation

Beti Kristinawati,
Nyofan Wahyu Mardana,
Nove Wiand Dwi Wijayanti

Abstract: Purpose: Determine the impact of education-based treatment on sustaining quality of life during COVID-19 adaptation. Designs: A randomized, 2-group, structured, holistic education-based intervention within eight weeks in preserving total quality of life (QoL) for hypertension patients with conventional care. Methods: Utilizing randomized controlled trials, 380 patients with hypertension are separated into two groups and evaluated. The patients are separated into two groups totaling 190 individuals each group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Furthermore, therapies with a holistic approach were evaluated for effectiveness in research (Utomo et al, 2024); the findings revealed that a holistic recovery program improves the quality of life of drug abusers. Several research has investigated aspects of environmental change associated with the COVID-19 pandemic, including ailments like hypertension (Kristinawati et al, 2023) and psychological disorders (Diannita et al, 2023;Sriati et al, 2023). Kristinawati's intervention in educationbased treatment can preserve quality of life throughout COVID-19, and digital-based psychotherapy in overcoming psychological problems carried out in Sriati et al (2023) research on college students has successfully aided adaptability to the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…Furthermore, therapies with a holistic approach were evaluated for effectiveness in research (Utomo et al, 2024); the findings revealed that a holistic recovery program improves the quality of life of drug abusers. Several research has investigated aspects of environmental change associated with the COVID-19 pandemic, including ailments like hypertension (Kristinawati et al, 2023) and psychological disorders (Diannita et al, 2023;Sriati et al, 2023). Kristinawati's intervention in educationbased treatment can preserve quality of life throughout COVID-19, and digital-based psychotherapy in overcoming psychological problems carried out in Sriati et al (2023) research on college students has successfully aided adaptability to the COVID-19 pandemic.…”
mentioning
confidence: 99%